HMG CoA reductase inhibitors - Feussner, Giso (Current opinion in lipidology, 1994)
Beta-hydroxy-β-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors (HMG CoA RIs) are now being prescribed in many different countries, and the number of patients treated with these compounds is estimated to be over 1.5 million. The spectrum of indications for these drugs is enlarging. Thus, not only patients with primary hypercholesterolemia are suitable candidates for therapy with HMG CoA RIs, but also patients with other forms of familial and non-familial (secondary) dyslipidemias. The safety and tolerance profile is remarkably good and adverse effects tend to be mild and rare. Currently, several primary and secondary intervention trials are ongoing or in preparation to investigate the influence of HMG CoA RIs on cardiovascular morbidity and mortality.
Gesehen am 30.01.2025